2004
DOI: 10.1093/molehr/gah021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch activates type 2 cyclooxygenase via activator protein-1 transcription factor in human myometrial cells

Abstract: The uterus is subject to stretch throughout pregnancy, which, in the presence of progesterone, is a potent stimulus for uterine growth. However, in the absence of progesterone or when stretch is excessive, as in multiple pregnancy, it may provoke the onset of labour. We have investigated the effect of stretch on prostaglandin synthesis in primary human uterine myocytes [non-pregnant (NP), pregnant not in labour (NL) and pregnant in labour (L)]. The cells were grown on flexible bottom culture plates and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 21 publications
6
80
1
Order By: Relevance
“…stretch upregulated IL-8 and COX-2 in a MAPK-dependent manner (Loudon 2004, Sooranna 2004. Later studies confirmed that stretch of myometrial cells increased the expression and release of while showing that other chemokines and inflammatory cytokines are also increased in a predominantly NFkBdependent manner (Hua et al 2012).…”
Section: :3mentioning
confidence: 93%
“…stretch upregulated IL-8 and COX-2 in a MAPK-dependent manner (Loudon 2004, Sooranna 2004. Later studies confirmed that stretch of myometrial cells increased the expression and release of while showing that other chemokines and inflammatory cytokines are also increased in a predominantly NFkBdependent manner (Hua et al 2012).…”
Section: :3mentioning
confidence: 93%
“…In human myometrial cells, the MAPK pathways are also implicated in the induction of COX-2 expression (PGHS2/PTGS2; Bartlett et al 1999, Sooranna et al 2004 and in mediating the effects of OT (Zhong et al 2003) and corticotropin-releasing hormone (CRH) (Grammatopoulos et al 2000, Papadopoulou et al 2004. Increasing maternal plasma levels of CRH during the last weeks of pregnancy and the substantial expression of CRH receptors in choriodecidua, placenta and myometrium suggests that this stress hormone plays a role in the control of human parturition (Sehringer et al 2004).…”
Section: Mapk-signaling Pathwaymentioning
confidence: 99%
“…Our observation that cyclic stretch increased COX-2 mRNA expression, while decreasing COX-1 mRNA expression, is in line with a predominant role for COX-2 in stretch-induced inflammation in the lung. In addition, COX-2 mRNA expression has been shown to be upregulated by mechanical loading in various cell types (16,25,32,43). Thus it appears that COX-2 is the predominant cyclooxygenase isoform regulating the mechanoproduction of prostanoids in the lung epithelium.…”
Section: Ajp-lung Cell Mol Physiolmentioning
confidence: 99%
“…Cyclic stretching of fetal lung cells had a similar effect (42). In addition to lung cells, uterine myometrial cells, tendon fibroblasts, macrophages, and osteoblasts have all been shown to increase their prostanoid production because of increased mechanical stress (16,25,32,43). Thus mechanostimulation of prostanoid production and/or release may be a conserved event in the evolution of the inflammatory response triggered by mechanical forces.…”
mentioning
confidence: 91%